The application of Boolean algebra in modelling of leakage condition of a car hydraulic braking system - Idzikowski, Adam; Salamon, Szymon (Zielona Góra: Uniwersytet Zielonogórski)
A general characteristics of a car hydraulic braking system (CHBS) is presented in this publication. A graphical model of properties-component objects is developed for the above-mentioned system. Moreover, four mathematical models in terms of logic, the set theory and the Boolean algebra of Boolean functions are developed. The examination is ended with a general model of the CHBS for n - Boolean variables and the construction and mathematical-technical interpretation of this model is presented.
Keywords: braking system; hydraulic circuit; leakage; Boolean algebra; modelling